1988
DOI: 10.4141/cjss88-011
|View full text |Cite
|
Sign up to set email alerts
|

Rooting Characteristics of Corn, Soybeans and Barley as a Function of Available Water and Soil Physical Characteristics

Abstract: Blocks were removed at 0.15-m depth increments until no further roots were observed. All roots were identified by eye, hand picked from the soil, stained with Congo red (Ward et al. 1978) and their length estimated using the grid technique tested by Tennant (1975

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
31
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 7 publications
11
31
0
Order By: Relevance
“…Hund et al, (2009) observed greater rooting depth in the drought tolerant tropical maize inbred lines than the sensitive lines. An inverse relationship between rooting depth and available soil water was reported in maize under field conditions (Dwyer et al, 1988). Earlier Ogawa et al, (2005) also reported declined root length and roots density in maize in water deficit environment.…”
Section: Root Traits Under Greenhouse Conditionsmentioning
confidence: 99%
“…Hund et al, (2009) observed greater rooting depth in the drought tolerant tropical maize inbred lines than the sensitive lines. An inverse relationship between rooting depth and available soil water was reported in maize under field conditions (Dwyer et al, 1988). Earlier Ogawa et al, (2005) also reported declined root length and roots density in maize in water deficit environment.…”
Section: Root Traits Under Greenhouse Conditionsmentioning
confidence: 99%
“…Drought stress is the largest single factor limiting crop productivity globally (Pennisi, 2008), and is influenced by tillage because of its impact on rooting depth and root density distribution (Dwyer et al, 1988;Barber & Kovar, 1991). The distribution of water within the soil profile, an important determinant of corn root distribution, is also affected by tillage (Lahai & Ekanayake, 2009).…”
mentioning
confidence: 99%
“…In spite of these drawbacks the combination of O 2 contents and TDR water contents have provided some added insight on earlier root growth analyses. Dwyer et al (1988Dwyer et al ( , 1996 investigated root growth and development, and observed a sharp drop in rooting activity at depths in the 20-to 40-cm range. In addition, they showed that root growth was slowed at profile soil water contents at or above field capacity (Dwyer et al 1988).…”
Section: Discussionmentioning
confidence: 99%